1964
DOI: 10.1126/science.143.3612.1334
|View full text |Cite
|
Sign up to set email alerts
|

Brucella -Agglutinating Antibodies: Relation of Mercaptoethanol Stability to Complement Fixation

Abstract: Brucella-agglutinating antibodies from selected bovine blood serums and milk samples did not fix complement, and after treatment with 2-mercaptoethanol they lost agglutinating power. After infection of calves with Brucella abortus, strain 19, agglutinins for Brucella that were inactivated by mercaptoethanol appeared earlier than those stable to mercaptoethanol. Under the conditions of these experiments, the appearance and development of complement-fixing capacity coincided closely with the mercaptoethanol stab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
13
0

Year Published

1967
1967
2003
2003

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(13 citation statements)
references
References 15 publications
0
13
0
Order By: Relevance
“…The former workers showed that three purified immunoglobulins, known as IgG, IgA, andIgM, obtained from the serum of cases of brucellosis contained brucella agglutinating antibodies, and Wilkinson, using mainly cattle sera, found that when each of these immunoglobulins was removed by specific precipitating rabbit anti-human IgG, IgA, and IgM sera this resulted in .he inhibition of their serological activity. Anderson et al '1964) and Reddin et al (1965) reported changes in serological activity during the course of the disease, and it seemed likely that analysis of a serum at different stages of the disease to letermine in which fraction its serological activity lies might give information of value in diagnosis, as has been indicated in a previous study (Kerr et al, 1966).…”
mentioning
confidence: 86%
“…The former workers showed that three purified immunoglobulins, known as IgG, IgA, andIgM, obtained from the serum of cases of brucellosis contained brucella agglutinating antibodies, and Wilkinson, using mainly cattle sera, found that when each of these immunoglobulins was removed by specific precipitating rabbit anti-human IgG, IgA, and IgM sera this resulted in .he inhibition of their serological activity. Anderson et al '1964) and Reddin et al (1965) reported changes in serological activity during the course of the disease, and it seemed likely that analysis of a serum at different stages of the disease to letermine in which fraction its serological activity lies might give information of value in diagnosis, as has been indicated in a previous study (Kerr et al, 1966).…”
mentioning
confidence: 86%
“…Detection of specific IgM antibodies in ELISA is useful in diagnosing patients with acute illness, given the fact that the IgM antibody response tends to develop somewhat earlier than the IgG response. IgM detection also is used to discriminate between acute and chronic diseases, and for this SAT has been used as well (2,16,22). A significant reduction in titer in this assay when performed in the presence of reducing agent indicates the presence of specific IgM antibodies.…”
mentioning
confidence: 99%
“…abortus infection. However, the agglutinin levels decline in the chronic phase of the disease, probably because of shift in the pattern of immunoglobulin response (Anderson et al, 1964 ;Rice, Tailyour and Cochrane, 1966). Nevertheless, precipitins persist for very long periods, possibly for the duration of infection (Corbel, to be published), suggesting that differences in immunodiffusion patterns might be used to distinguish between the antibody responses to 45/20 vaccine and active infection.…”
Section: Discussionmentioning
confidence: 99%
“…
CONSIDERABLE attention has been paid to the selection of diagnostic procedures for differentiation of antibodies resulting from vaccination of cattle with Brucella abortus, strain 19, from those resulting from natural infection (Yuskovets, 1956;Anderson et al, 1964;Rose and Amerault, 1964;Schimmel and Erler, 1967). Relatively less attention has been given to the problems in diagnosis arising from the use of Br.
…”
mentioning
confidence: 99%